Association between dietary folate intake and gestational diabetes mellitus: evidence from baseline data of a Chinese maternal and infant cohort - Wu, Xiangyi; Zhang, Rong; Lu, Lu; Fan, Rui; Hu, Rui; Teng, Yue; Pan, Lina; Zeng, Xiaoling; Jiang, Wei; Li, Wei; Dong, Ling; Zhang, Zhaofeng; et al. (Frontiers in Nutrition, 2025)
IntroductionFolate is an essential nutrient during pregnancy, which may contribute to the development of gestational diabetes mellitus (GDM), but the results of existing studies are inconsistent. This study aimed to assess the dietary folate intake among pregnant women and examine its association with GDM.MethodBaseline data from the Mother & Child Nutrition and Health Cohort Study (MCNHC) were used in this cross-sectional analysis, which women with 24–30 weeks of gestation were included. Dietary folate intake was measured and their status was categorized by national guidelines. Methyl-donor nutritional quality index (MNQI) was used as a comprehensive indicator to assess the intake of folate and corelative nutrients in one-carbon metabolism. Binary logistic regression analysis was used to investigate the associations between dietary folate intake and GDM.ResultsAmong the 368 pregnant women included, 147 women (39.9%) were diagnosed with GDM. The proportion of participants with insufficient dietary folate intake (< 520 μg DFE/d) was 57.5%. While no significant association was observed between dietary folate intake and GDM, the highest odds of GDM was observed in women with combined insufficient vitamin B12 intake and folate intake in the highest quartile (p < 0.05).DiscussionIn Conclusion, insufficient dietary folate intake in Chinese pregnant women during the second and third trimesters is rather concerning. It points out an urge for improving the dietary folate intake among pregnant women during this period. It also suggests a potential association between balanced vitamin B12 and folate intake and a lower likelihood of GDM.